THE PERCEPTIONS OF STUDENTS OF THE FACULTY OF ECONOMICS AND SOCIAL SCIENCES AT THE UNIVERSITY LIBRARY'S CIRCULATION SERVICE SARI MUTIARA INDONESIA - Ridlo, Muhammad Rasyid; Marajari, Muhammad Rinaldo; Bebe, Paulina Inya (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2019)
Background of Study: The rapid development of science and information makes it easy for everyone to access everything that exists. The library is one of the supporting factors in the existing civilization, which is a filter of information to be announced.Purpose: This research was conducted at the Sari Mutiara University Library Indonesia with the aim to find out how the Student Perception of the Faculty of Economics and Social Sciences on circulation services.Method: The method used in this study is descriptive method with the population of this study are members of the library from 2015 to 2018, amounting to 157 people and the sample taken as many as 113 people based on Slovin formula.Finding: The results showed that the perceptions of students of the Faculty of Economics and Social Sciences on circulation services in the library of Sari Mutiara Indonesia University were good (75.2%), but still needed improvement in the provision of up-to-date collections, book lending provisions, suitability of collections with library needs, loan period, time available and number of books that can be borrowed.Conclution: To realize the best service for students, the Sari Mutiara Indonesia University Library is recommended to further improve the quality and quantity of both officers and collections as well as to add supporting facilities for library services so as to attract the interest of visitors to come to visit the library